Wasiat Sebagai Penyeimbang Pembagian Warisan Menurut Hazairin Perspektif Teori Keadilan Distributif Aristoteles - Muhammad Misbakhul Ulum; Zaenul Mahmudi; Moh. Toriquddin (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
The division of inheritance is a problem that will be faced by every family of Muslims.Jumhur ulama has established a method of division of property, namely by the method of inheritance. However, Hazairin has his own thought that the distribution of inheritance is not only done by inheritance method, but can also be compromised with a will in order to provide justice for each existing heir. This study aims to examine more deeply about the method offered by Hazairin, whether it can provide justice for the heirs or not. Therefore, a deeper study is needed using Aristotle's theory of distributive justice. The research uses a qualitative approach with the type of character study research, using secondary legal materials. The results showed that Hazairin's goal of making a will as a counterweight in the distribution of inheritance was to provide a share that was in accordance with the conditions of each heir, both in terms of weaknesses and strengths that were not considered in the inheritance system. Furthermore, the method initiated by Hazairin has met the indicators of Aristotle's distributive justice including being in accordance with the law, impartial, and proportional.